On fraud and certification of corporate social responsibility - Carmen Arguedas; Esther Blanco (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
We analyze the strategic decision of firms to voluntarily certify corporate social responsibility (CSR) practices in a context where other firms can falsely pretend to be socially responsible. Equilibrium outcomes are crucially determined by consumers' beliefs about the credibility of firms' CSR claims, which depend in turn on the (expected) fines for fraud. First, we show that an increase in such fines extends the likelihood of firms investing in CSR, at the expense of a reduced likelihood of certification. Second, fraud only arises when the fines for fraud are at intermediate levels and some CSR firms do not certify their practices. Third, the presence of fraud comes at a cost for firms by inducing lower equilibrium prices than in settings with honest marketing. Forth, the coexistence of fraud and certification induces differentiation price premia below marginal production costs and certification price premia above marginal certification costs. Lastly, social welfare rises as fines for fraud increase.
Keywords: C72; D43; H23; Q58; 330; corporate social responsibility; credence goods; certification; fraud